Eksistensi Kotak Kosong dalam Pemilihan Kepala Daerah terhadap Sistem Demokrasi Lokal - Alyonni, Alvin; Soerjatisnanta, Hieronymus; Yusdiyanto, Yusdiyanto; Muhtadi, Muhtadi (Penerbit Goodwood, 2025)
Purpose: This study investigates the legal legitimacy and democratic consequences of the “empty box” (kotak kosong) mechanism in Indonesia’s local elections, particularly in uncontested single-candidate regional head races. The increasing frequency of such elections raises concerns regarding diminished political competition, legitimacy, and voter choice within Indonesia’s democratic processes. Methodology/approach: This study adopts a normative juridical approach by analyzing statutory laws, especially Law No. 10 of 2016, and key Constitutional Court rulings, such as Decision No. 100/PUU-XIII/2015. Additionally, this study incorporates secondary data from relevant local election cases and academic literature published between 2016 and 2024. Results/findings: The findings reveal that the empty box mechanism is legally acknowledged and constitutionally permitted as a tool for democratic resistance. However, its increasing usage reflects systemic problems: weak internal democracy among political parties, the dominance of political elites, and the absence of viable alternatives. These factors contribute to declining electoral competitiveness and limit the meaningful participation of voters. Conclusions: While the empty box offers a symbolic form of dissent, it does not resolve deeper structural constraints undermining local democratic processes. This mechanism highlights dissatisfaction but fails to generate substantive democratic alternatives. Limitations: This study is limited to doctrinal legal analysis and case study reviews without empirical field research, which may restrict the generalizability of its findings to other countries. Contribution: This study contributes to the ongoing discourse on electoral reform in transitional democracies by assessing the empty box as an instrument of political expression and identifying the need for structural democratic improvements.